2021
DOI: 10.1002/cac2.12146
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of long non‐coding RNAs in the progression of esophageal cancer

Abstract: Esophageal cancer (EC) is one of the most common malignant tumors of the digestive system with high incidence and mortality rate worldwide. Therefore, exploring the pathogenesis of EC and searching for new targeted therapies are the current research hotspot for EC treatment. Long non‐coding RNAs (lncRNAs) are endogenous RNAs with more than 200 nucleotides, but without protein‐coding function. In recent years, lncRNAs have gradually become the focuses in the field of non‐coding RNA. Some lncRNAs have been prove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 99 publications
0
12
0
Order By: Relevance
“…Increasing evidence reveals lncRNAs play a critical role in ESCC progression [ 21 ]. Besides well-characterized lncRNAs, potential critical lncRNAs mediating ESCC formation and progression should be examined.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence reveals lncRNAs play a critical role in ESCC progression [ 21 ]. Besides well-characterized lncRNAs, potential critical lncRNAs mediating ESCC formation and progression should be examined.…”
Section: Discussionmentioning
confidence: 99%
“…Esophageal squamous cell carcinoma (ESCC) is the sixth leading cause of cancer death worldwide (57,58). To advance the study of non-invasive biomarker detection, Lin et al (59) extracted and analyzed the G-Nchirna in exosomes from the tissues and saliva of mice and ESCC patients.…”
Section: Esophageal Squamous Cell Carcinomamentioning
confidence: 99%
“…Esophageal squamous cell carcinoma (ESCC) is the sixth leading cause of cancer death worldwide ( 57 , 58 ). To advance the study of non-invasive biomarker detection, Lin et al.…”
Section: Applications In Cancer Researchmentioning
confidence: 99%
“…It has been proved that lncRNAs play important roles in the pathogenesis of different types of tumors (e.g., ovarian cancer, clear renal cell carcinoma, and colorectal cancer) by regulating target gene expression [ 9–13 ]. Recently, accumulated evidence suggested that many lncRNAs are dysregulated in EC and regulate cell proliferation, apoptosis, and metastasis [ 14 ]. Vascular endothelial growth factor C ( VEGFC ) mRNA stability–associated long noncoding RNA (lncRNA VESTAR) promotes lymphangiogenesis and lymph node metastasis of ESCC by enhancing VEGF-C mRNA stability [ 15 ].…”
Section: Introductionmentioning
confidence: 99%